Astaxanthin Counteracts Excitotoxicity and Reduces the Ensuing Increases in Calcium Levels and Mitochondrial Reactive Oxygen Species Generation - Francisca García; Pedro Lobos; Alejandra Ponce; Karla Cataldo; Daniela Meza; Patricio Farías; Carolina Estay; Felipe Oyarzun-Ampuero; Rodrigo Herrera-Molina; Andrea Paula-Lima; Álvaro O. Ardiles; Cecilia Hidalgo; et al. (Marine Drugs, 2020)
Astaxanthin (ASX) is a carotenoid pigment with strong antioxidant properties. We have reported previously that ASX protects neurons from the noxious effects of amyloid-β peptide oligomers, which promote excessive mitochondrial reactive oxygen species (mROS) production and induce a sustained increase in cytoplasmic Ca2+ concentration. These properties make ASX a promising therapeutic agent against pathological conditions that entail oxidative and Ca2+ dysregulation. Here, we studied whether ASX protects neurons from N-methyl-D-aspartate (NMDA)-induced excitotoxicity, a noxious process which decreases cellular viability, alters gene expression and promotes excessive mROS production. Incubation of the neuronal cell line SH-SY5Y with NMDA decreased cellular viability and increased mitochondrial superoxide production; pre-incubation with ASX prevented these effects. Additionally, incubation of SH-SY5Y cells with ASX effectively reduced the basal mROS production and prevented hydrogen peroxide-induced cell death. In primary hippocampal neurons, transfected with a genetically encoded cytoplasmic Ca2+ sensor, ASX also prevented the increase in intracellular Ca2+ concentration induced by NMDA. We suggest that, by preventing the noxious mROS and Ca2+ increases that occur under excitotoxic conditions, ASX could be useful as a therapeutic agent in neurodegenerative pathologies that involve alterations in Ca2+ homeostasis and ROS generation.